Evaluating the effects, implementation experience and political economy of primary healthcare facility autonomy reforms within counties in Kenya: a mixed methods study protocol - Edwine Barasa; Benjamin Tsofa; Anita Musiega; Jacinta Nzinga; Anne Musuva; Nirmala Ravishankar; Wangari Ng'ang'a; Gillian Turner; Beatrice Amboko; Peter Mwangi Mugo; Beryl Maritim; Ethan Wong; et al. (BMJ Public Health)
Introduction There is a growing emphasis on improving primary healthcare (PHC) services and granting frontline service providers more decision-making autonomy. In October 2023, Kenya enacted legislation mandating nationwide facility autonomy. There is limited understanding of the effects of health facility autonomy on PHC facilities performance. It is recognised that stakeholder interests influence reforms, and gender plays a critical role in access to health and its outcomes. This protocol outlines the methods for a study that plans to evaluate the effects, implementation experience, political economy and gendered effects of health facility autonomy reforms in Kenya.Methods and analysis The research will use a before-and-after quasi-experimental study design to measure the effects of the reform on service readiness and service utilisation and a cross-sectional qualitative study to explore the implementation experience, political economy and gendered effects of these reforms. Data to measure the effects of autonomy will be collected from a sample of 80 health facilities and 1600 clients per study arm. Qualitative interviews will involve approximately 83 facility managers and policymakers at the county level, distributed across intervening (36) and planning to intervene (36) counties. Additionally, 11 interviews will be conducted at the national level with representatives from the Ministry of Health, the National Treasury, the Controller of Budget, the Council of Governors, the Auditor General and development partners. Given the uncertainty surrounding the implementation of the reforms, this study proposes two secondary designs in the event our primary design is not feasible—a cross-sectional study and a quasi-experimental interrupted time series design. The study will use a difference-in-difference analysis for the quantitative component to evaluate the effects of the reforms, while using thematic analysis for the qualitative component to evaluate the political economy and the implementation experience of the reforms.Ethics and dissemination This study was approved by the Kenya Medical Research Institute Scientific and Ethics Review Unit (KEMRI/SERU/CGMR-C/294/4708) and the National Commission for Science, Technology and Innovation (NACOSTI/P/23/28111). We plan to disseminate the findings through publications, policy briefs and dissemination workshops.